PENERAPAN MEDIASI PENAL TERHADAP TINDAK PIDANA PENGANIAYAAN DI KEPOLISIAN RESORT KOTA PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
This criminal law perspective in Indonesia is already familiar with the settlement of criminal cases outside the court, or often called Penal Mediation. This is sought to uphold Restorative justice by balancing the actions of the perpetrators of criminal acts with the consequences. Reference for the implementation of penal mediation refers to Pancasila, the 1945 Constitution (UUD), Law number 8 of 1981 concerning the Criminal Procedure Code (KUHAP), Law No. 2 of 2002 concerning the Indonesian National Police. Police Chief's Letter No. B / 3022 / XXI / 2009 / SDEOPS which explains that cases that have been resolved through Alternative Dispute Resolution in order to avoid. Penal Mediation is a legal breakthrough applied by law enforcement officials with reference to the process of Restorative Justice approach, bearing in mind that there is an objective to reconcile victims of crime with mediators through mediation in order to settle cases, return and repair damage and losses caused by a criminal case. Victims and perpetrators are expected to find and reach the best solutions and alternatives to resolve the case This research uses the typology of sociological legal research or also called non-doctrinal legal research, which is more specifically about the effectiveness of law. In this study the authors used the descriptive nature of the study, because the authors describe how the application of penal mediation to acts of abuse in the Pekanbaru. The results of research conducted by the author are, firstly, the implementation of the application of the mediation of the penalties against the criminal acts of persecution, then to find out what legal consequences are caused and what obstacles occur when the application of the mediation of the penalties. The resort is obliged to determine which cases of abuse are entitled to be mediated. Keywords: Penal Mediation - Criminal Acts of Abuse